Effects of copper, nickel and lead on growth parameters and antioxidative defense system of Solanum lycopersicum L. - Kumari, Anjana; Nagpal, Avinash Kaur; Katnoria, Jatinder Kaur (Current Botany, 2024)
The current study assessed the effects of lead (Pb), copper (Cu), and nickel (Ni) in roots and shoots on growth indices, the antioxidative defense system, and metal uptake in Solanum lycopersicum L. variety Punjab Kesar Cherry. For 60 days, S. lycopersicum seeds were exposed to varying amounts of three metals (0-100 μM of Cu and 0-60 μM of Ni and Pb). In comparison to the control, the percentage of germination, root and shoot length, and fresh and dry weight of the roots and shoots all decreased, according to the results. The bioaccumulation factor of both roots and shoots, along with the translocation factor, increased at lower concentrations and decreased at higher concentrations; for Pb, on the other hand, the translocation factor increased with increasing concentrations. At 60 μM, the order of the bioaccumulation factor was Cu>Ni>Pb for roots, and Cu>Pb>Ni for shoots. The antioxidative enzyme activities, including ascorbate peroxidase (APX), catalase (CAT), dehydro ascorbate reductase (DHAR), glutathione reductase (GR), glutathione S transferase (GST), peroxidase (POD), and superoxide dismutase (SOD), were increased at lower concentrations and decreased at higher concentrations under Cu, Ni, and Pb treatments. The order of toxicity in terms of decrease in protein content was observed as Pb>Ni>Cu for both roots and shoots.